2021
DOI: 10.1039/d1cp03565g
|View full text |Cite
|
Sign up to set email alerts
|

A first-principles study of two-dimensional NbSe2H/g-ZnO van der Waals heterostructures as a water splitting photocatalyst

Abstract: Based on first-principles calculations, we propose a new two-dimensional (2D) van der Waal (vdW) heterostructure that can be used as a photocatalyst for water splitting. The heterostructure consists of vertically...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…From theoretical work, a handful of 2D heterostructures have been studied. For example, through first-principles calculations, MoS 2 /g-C 3 N 4 , InSe/SiH, NbSe 2 H/ZnO, MoSe 2 /SnSe 2 and WSe 2 /SnSe 2 heterostructures were predicted to be a good photocatalyst for water-splitting due to the favourable band edge alignment [23][24][25][26]. Furthermore, theoretical studies have also shown that the electronic and optical properties of heterostructures formed using AlAs/germanene, silicene/arsenene and InSb/InSe can be modulated by external electric field and strain [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…From theoretical work, a handful of 2D heterostructures have been studied. For example, through first-principles calculations, MoS 2 /g-C 3 N 4 , InSe/SiH, NbSe 2 H/ZnO, MoSe 2 /SnSe 2 and WSe 2 /SnSe 2 heterostructures were predicted to be a good photocatalyst for water-splitting due to the favourable band edge alignment [23][24][25][26]. Furthermore, theoretical studies have also shown that the electronic and optical properties of heterostructures formed using AlAs/germanene, silicene/arsenene and InSb/InSe can be modulated by external electric field and strain [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…12,13 To rationally build a heterostructure for global solar water splitting, three fundamental rules must be considered: (i) the sun can be utilized advantageously, (ii) the band edges are properly oriented with respect to the redox potentials of water, and (iii) slower electron−hole pair recombination and subsequent separation of photogenerated carriers. Several 2D heterostructures 12,13 have been presented thus far as catalysts for photocatalytic water splitting. It remains difficult to create a suitable photocatalyst with high activity and stability for hydrogen production despite experimental and theoretical efforts to do so.…”
Section: Introductionmentioning
confidence: 99%
“…Several 2D heterostructures , have been presented thus far as catalysts for photocatalytic water splitting. It remains difficult to create a suitable photocatalyst with high activity and stability for hydrogen production despite experimental and theoretical efforts to do so.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…81,83,84 In addition, the electronic structure of these materials can be tailored by engineering their bandgap and doping, enabling them to absorb light in the visible range and enhance their photoactivity. 85,86 Several types of heterostructures have been investigated for electro-/ photo-catalytic water splitting, including vertical or lateral stacking, [87][88][89][90] core-shell structuring, [91][92][93][94][95] chemical vapor deposition (CVD), [96][97][98][99] electrodeposition, [100][101][102] in-plane epitaxial growth, co-precipitation, and liquid exfoliation. For example, a recent study reported graphitic carbon nitride (g-C 3 N 4 )@NiO nanocomposites for enhancing the PEC activity of g-C 3 N 4 with unique slack dynamics of charge transfer between layers, where NiO was used as a 2D modifier.…”
Section: Introductionmentioning
confidence: 99%